2(3x-2)-3(x+1)=3

Simple and best practice solution for 2(3x-2)-3(x+1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-2)-3(x+1)=3 equation:


Simplifying
2(3x + -2) + -3(x + 1) = 3

Reorder the terms:
2(-2 + 3x) + -3(x + 1) = 3
(-2 * 2 + 3x * 2) + -3(x + 1) = 3
(-4 + 6x) + -3(x + 1) = 3

Reorder the terms:
-4 + 6x + -3(1 + x) = 3
-4 + 6x + (1 * -3 + x * -3) = 3
-4 + 6x + (-3 + -3x) = 3

Reorder the terms:
-4 + -3 + 6x + -3x = 3

Combine like terms: -4 + -3 = -7
-7 + 6x + -3x = 3

Combine like terms: 6x + -3x = 3x
-7 + 3x = 3

Solving
-7 + 3x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3x = 3 + 7

Combine like terms: -7 + 7 = 0
0 + 3x = 3 + 7
3x = 3 + 7

Combine like terms: 3 + 7 = 10
3x = 10

Divide each side by '3'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| (C-2)(C-5)= | | y[n]-0.5*y[n-2]=0 | | 24/2=4/2x | | 44=2(4+3x)+2(4+5x) | | 2x(x+e)=3e(x+e) | | 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 | | 2y-4=29 | | y^2+11y+49=4 | | x((3x-3)(2x-8)+(2x+2)(3x+1))=(5x-5)(3x+1)(2x-8) | | ln(x)=-x+2 | | x^2+y^2-2y=3 | | 20log(3x)=49 |

Equations solver categories